2016
DOI: 10.1177/0363546516651613
|View full text |Cite
|
Sign up to set email alerts
|

Medialized Clavicular Bone Tunnel Position Predicts Failure After Anatomic Coracoclavicular Ligament Reconstruction in Young, Active Male Patients

Abstract: The optimal technique for treating acromioclavicular separations has yet to be determined. Recently, anatomic coracoclavicular reconstruction has demonstrated biomechanical superiority to previously described methods. The findings of optimal tunnel positioning in anatomic reconstructions from this large active-duty military cohort can assist preoperative planning to reduce failure rates when treating these difficult injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
(63 reference statements)
1
25
0
Order By: Relevance
“…The surgeon should avoid medializing the clavicular tunnel. 8,10 Cook et al 8 reported that no failures occurred if the conoid tunnel was <25% of the clavicular length from the lateral edge of the clavicle. In the current study, we created the trapezoid and conoid clavicular bone tunnels at 1.5 mm and 2.5 mm from the lateral edge of the clavicle, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon should avoid medializing the clavicular tunnel. 8,10 Cook et al 8 reported that no failures occurred if the conoid tunnel was <25% of the clavicular length from the lateral edge of the clavicle. In the current study, we created the trapezoid and conoid clavicular bone tunnels at 1.5 mm and 2.5 mm from the lateral edge of the clavicle, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Cook JB et al [12] recommend through a series of 130 patients the positioning of the conoid tunnel at 25% and trapezoid tunnel at 17% of the total clavicular length from its lateral border. Eisenstein ED et al [13] considered that the optimal ratio of the conoid tunnel should be between 0.20 and 0.25 and the ratio of trapezoid tunnel should be less than 0.16. In addition, anteroposterior stability remains poorly controlled with this procedure, as reported by several authors [14,15] who describe a partial loss of reduction which is accompanied by a decrease in the functional score.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated increased failure rates with a medialized clavicular bone tunnel position in AC ligament reconstruction. 4,7 Cook et al 4 demonstrated early radiographic failure in a young military population (sex was not specified) with a conoid tunnel ratio of greater than 0.3 and recommended placing the conoid tunnel at 25% of the total clavicular length. Eisenstein et al 7 reviewed 38 male patients in whom 20 radiographic failures were noted; the investigators recommended that optimal tunnel placement would be between 20% and 25% of total clavicular length.…”
Section: Discussionmentioning
confidence: 99%